Analysis of the Level of Satisfaction of Rice Farmers towards the Performance of Agricultural Extension Workers in Muaradua Kisam District, South Oku Regency - Dunan, Hendri Dunan; Munajat, Munajat; Sari, Fifian Permata (ITScience (Information Technology and Science), 2025)
Agricultural extension is an important and strategic activity that cannot be separated from development in the agricultural sector. Agricultural extension is the spearhead of development at the field level, which also determines the development of the farming system run by farmers or farmer groups. One indicator of the role of agricultural extension is the development of farmer groups, which is shown through their abilities in terms of both technical and management of the farming business being run. This research aims to analyze the level of satisfaction of rice farmers with the role of Field Agricultural Instructors (PPL) in increasing farming productivity in Muaradua Kisam District, South Ogan Komering Ulu (OKU) Regency. The research used a survey method with a simple random sampling technique, where 60 lowland rice farmers from a total population of 120 farmers were used as respondents. Data was collected through questionnaires and interviews and then analyzed using a descriptive approach. The research results show that most of the attributes of extension services have met the level of farmer satisfaction, especially in providing extension services with a friendly attitude and the application of farming technology. However, there are several attributes, such as organizing farmer groups and providing complete technological information, which do not fully satisfy farmers. This conclusion indicates the need to increase the capacity of extension workers in building effective communication and cooperation to increase farmer satisfaction and support the sustainable development of the agricultural sector in the research area.